MODEL PEMBELAJARAN COOPERATIVE PROJECT BASED LEARNING DALAM MENURUNKAN DEMOTIVASI BELAJAR MAHASISWA PASCA PANDEMI - Putri, Ellyana Ilsan Eka; Masruroh, Fitriatul (Tarbiyatuna Kajian Pendidikan Islam, 2023)
Researchers have been learning innovative design modifications based on conditions students in Islamic education of early childhood of IAI Ibrahimy Genteng Banyuwangi called cooperative project based learning (CPBL). CPBL designed to give room for college students have been the motivation to improve when. Learning special consideration to prodi piaud as the subject of research is that students Islamic education of early childhood of IAI Ibrahimy dominated early childhood teachers not 75 with undergraduate degrees and percent has married so researchers seen so many factors affect the demotivasi. Assessing the efficacy approach cooperative project based learning done on the psychological capital (psycap) and student achievement. Researchers conducted to compare received treatment on an individual basis and do not get treatment. Learning researchers also measure the impact on student achievement through CPBL psycap with corelational method dan bootstrap technic.